Hannah Arendt and the Politics of Friendship - Nixon, Jon (Bloomsbury Academic, 2015)
This book is available as open access through the Bloomsbury Open Access programme and is available on www.bloomsburycollections.com. For Hannah Arendt, friendship had political relevance and importance. The essence of friendship, she believed, consisted in discourse, and it is only through discourse, she argued, that the world is rendered humane. This book explores some of the key ideas in Hannah Arendt's work through a study of four lifelong friendships -- with Heinrich Blücher, Martin Heidegger, Karl Jaspers and Mary McCarthy. The book draws on correspondence from both sides, illuminating our understanding of the social contexts within which Arendt's thinking developed and was clarified. It offers a cultural history of ideas: shedding light on two core ideas in Arendt - of 'plurality' and 'promise', and on how those particular ideas emerged through a particular set of relationships, at a significant moment in the history of the West. This book offers an original and accessible 'way in' to Arendt's work for students and scholars of politics, philosophy, intellectual history and literature.